TALIWANG-SASAK CODE-MIXING USED AMONG LUNYUK SPEECH COMMUNITY IN SUMBAWA BARAT - Arnis Alfiani, Medina; Soepriyanti, Henny; Amrullah, Amrullah (Universitas Hamzanwadi, 2024)
The Taliwang and Sasak languages ​​are an integral part of the cultural and linguistic identity of the West Nusa Tenggara region in Indonesia. These languages ​​serve not only as media of communication but also as carriers of cultural heritage, reflecting their respective communities' values, traditions and history. Taliwang, primarily spoken by people in the Taliwang region, is deeply embedded in local culture and plays a vital role in its speakers' daily lives. Likewise, Sasak, the primary language of the Sasak people in Lombok, is an essential element of Sasak's cultural identity. This research adopts a qualitative case study approach to explore complex social phenomena such as code-mixing in specific communities. A case study allows an in-depth examination of the linguistic practices of the Lunyuk community, focusing on how and why speakers mix Taliwang and Sasak in their daily interactions. This research uses qualitative method to analyze the data. This data includes the types of code-mixing such as: insertion, alternation, and congruent lexicalization.